Longitudinal investigation of nasopharyngeal methicillin-resistant Staphylococcus aureus colonization in early infancy: The PATCH birth cohort study. (February 2017) - Tsai, M.-H.; Chiu, C.-Y.; Shih, H.-J.; Liao, S.-L.; Hua, M.-C.; Huang, S.-H.; Yao, T.-C.; Lai, S.-H.; Huang, T.-S.; Yeh, K.-W.; Chen, L.-C.; Su, K.-W.; et al.
Abstract: Objectives: The study aimed to determine the long-term Staphylococcus aureus colonization patterns and strain relatedness, and the association between maternal and infant colonization in infancy. Methods: A birth cohort study was conducted from January 2012 to November 2014. Nasopharyngeal swabs for S. aureus detection were collected from infants at the age of 1, 2, 4, 6 and 12 months and from mothers when their children were 1-month-old. Results: In total, 254 samples were collected at each planned visit during the first 12-month study. The prevalence of S. aureus colonization decreased in the first year of life, ranging from 61.0% (155/254) at the age of 1 month to 12.2% (31/254) at 12 months. Persistent colonization, defined as a positive culture on four or five occasions, was detected in only 13.8% (35/254) of carriers. Most of the persistent carriers were colonized with methicillin-resistant S. aureus (MRSA) only, and among persistent MRSA carriers, 61.1% (11/18) had indistinguishable genotypes. Of the mothers with MRSA colonization, 77.1% (27/35) had infants who were concomitantly colonized at the age of 1 month; 70.4% (19/27) of the infant–mother paired isolates belonged to indistinguishable or related subtypes, which suggests that surrounding carriers, probably their mothers, may be the possible source for MRSA acquisition in early infancy. Conclusions: Staphylococcus aureus colonization including MRSA was commonly observed in our cohort. Strains of persistent MRSA among infant–mother pairs were usually of indistinguishable genotypes. Therefore, horizontal spread within households is possibly an important factor related to infant MRSA colonization.